Linoleic acid binds to SARS-CoV-2 RdRp and represses replication of seasonal human coronavirus OC43 - Anna Goc; Waldemar Sumera; Matthias Rath; Aleksandra Niedzwiecki (Scientific Reports, 2022)
Abstract Fatty acids belong to a group of compounds already acknowledged for their broad antiviral efficacy. However, little is yet known about their effect on replication of human coronaviruses. To shed light on this subject, we first screened 15 fatty acids, three lipid-soluble vitamins, and cholesterol, on SARS-CoV-2 RdRp, and identified the four fatty acids with the highest RdRp inhibitory potential. Among them, linoleic acid was found to have the greatest interaction with SARS-CoV-2 RdRp, with its direct binding to the cavity formed by the RNA double helix and protein. Linoleic acid forms hydrophobic interactions with multiple residues, and at the same time forms electrostatic interactions including the hydrogen bond with Lys593 and Asp865. In line with these results, a dose-dependent inhibition of HCoV-OC43 replication in vitro was observed, additionally strengthened by data from in vivo study, which also confirmed anti-inflammatory potential of linoleic acid. Based on these results, we concluded that our study provides a new understanding of the antiviral properties of fatty acids against human coronaviruses including the SARS-CoV-2 strain. Particularly, they lays down a new prospect for linoleic acid’s RdRp-inhibitory activity, as a candidate for further studies, which are warranted to corroborate the results presented here.